Teaching power yoga for sports - Lawrence, Gwen (Human Kinetics, 2019)
Show your athletes how power yoga can propel their performance to the next level. Teaching Power Yoga for Sports prepares you to develop and teach yoga programs that are directly relatable to specific sports and player positions, resulting in more resilient athletes who constantly compete at the top of their game